2007
DOI: 10.1177/0193945906297374
|View full text |Cite
|
Sign up to set email alerts
|

Parent Communication and Sexual Risk Among African Americans

Abstract: African American adolescents and young adults disproportionately experience adverse sexual health outcomes, including HIV, other sexually transmitted infections, and unintended pregnancy. Despite the diversity of the African American population, many studies of sexual risk are limited to inner-city and clinic samples. The purpose was to examine the influence of parent-teen sexual risk communication on the sexual risk attitudes, beliefs, and behaviors of 488 African American college students from a historically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 16 publications
8
98
3
1
Order By: Relevance
“…Conservative/Permissive Sexual Attitudes Nine studies showed that parent-adolescent sexual communication significantly predicted less permissive/more conservative attitudes toward engaging in sex (Cederbaum et al 2013;DiIorio et al 1999;Harris et al 2013;Holman and Kellas 2015;Hutchinson and Montgomery 2007;Kowal and Blinn-Pike 2004;Miller et al 1998;Moore and Davidson 1999;Treboux and Busch-Rossnagel 1995). Seven studies reported mixed findings (i.e., an empirical relation was only found for a meaningful subset of the sample and/or a particular variable of interest), which are detailed as follows.…”
Section: Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative/Permissive Sexual Attitudes Nine studies showed that parent-adolescent sexual communication significantly predicted less permissive/more conservative attitudes toward engaging in sex (Cederbaum et al 2013;DiIorio et al 1999;Harris et al 2013;Holman and Kellas 2015;Hutchinson and Montgomery 2007;Kowal and Blinn-Pike 2004;Miller et al 1998;Moore and Davidson 1999;Treboux and Busch-Rossnagel 1995). Seven studies reported mixed findings (i.e., an empirical relation was only found for a meaningful subset of the sample and/or a particular variable of interest), which are detailed as follows.…”
Section: Attitudesmentioning
confidence: 99%
“…Condom-use and Safe Sex Communication Efficacy Twelve studies reported a significant relation between parent-adolescent sexual communication and adolescents' greater perceived ability to acquire and use condoms or contraceptives (Harris et al 2013;Hutchinson et al 2003;Hutchinson and Cooney 1998;Hutchinson 2010;Kowal and Blinn-Pike 2004;Malcolm et al 2013;Mastro and Zimmer-Gembeck 2015), successfully negotiate the use of condoms with a resistant or new partner (DiClemente et al 2001;Hutchinson and Montgomery 2007;Kowal and Blinn-Pike 2004), and to discuss healthrelated topics such as STDs and AIDS with a current or hypothetical partner (DiIorio et al 2000;Sales et al 2007;Shoop and Davidson 1994). Three studies reported mixed findings: Fletcher et al (2015) found that receiving messages endorsing sex as normative predicted emerging adult women's greater condom-use efficacy, though messages endorsing sex as strictly relational or marital did not; Levin et al (2012) reported that the reception of sex-positive messages positively predicted condom-use and safe-sex communication efficacy in emerging adult men, but not women, and that the reception of abstinence messages predicted a decrease in the same for both emerging adult men and women; Lefkowitz and Espinosa-Hernandez (2007) reported that higher quality parent-adolescent sexual communication predicted fewer perceived barriers to using condoms, but receiving messages pertaining to dating, fertility issues, dangers of sex, and abstinence, were unrelated.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…African American female and male college students who reported high levels of parent communication about sex were less likely to have had current sexual activity than their counterparts who reported lower levels of communication (Hutchinson & Montgomery, 2007). Perhaps most importantly, in that same sample, female students reporting high levels of communication were more than 60% less likely to report having ever been pregnant than those reporting less communication (Hutchinson & Montgomery, 2007).…”
Section: Communication Research Examining Whether Communication Has mentioning
confidence: 82%
“…Perhaps most importantly, in that same sample, female students reporting high levels of communication were more than 60% less likely to report having ever been pregnant than those reporting less communication (Hutchinson & Montgomery, 2007).…”
Section: Communication Research Examining Whether Communication Has mentioning
confidence: 85%